The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/lno.10208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium and phosphorus limitation on the nutritional ecophysiology ofDaphnia

Abstract: Declines in environmental calcium (Ca) and phosphorus (P) concentrations have occurred over the past 30 yrs in lakes across the Canadian Shield in southern Ontario, and these reductions appear to be placing strong constraints on populations of Daphnia in this region. Here, we report results from a factorial manipulation of Ca concentrations and food P content under controlled laboratory conditions where we measured resulting changes in daphnid elemental content, individual growth and survival, and life history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 55 publications
6
54
0
Order By: Relevance
“…laboratory studies with D. magna , suggest that this species has a lower threshold of 0.5–1.0 mg Ca for survival, and that growth in juveniles, which have the highest specific Ca requirements, may be sub‐saturated <5 mg Ca L −1 (Alstad et al ; Hessen et al ), which would comprise 95% of Norwegian lakes. This corresponds well with the observed responses for D. pulex (Prater et al ). By using these species as examples of potential impacts of low—and declining—levels of Ca, it is evident that the effects even over a decadal time‐span may be profound.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…laboratory studies with D. magna , suggest that this species has a lower threshold of 0.5–1.0 mg Ca for survival, and that growth in juveniles, which have the highest specific Ca requirements, may be sub‐saturated <5 mg Ca L −1 (Alstad et al ; Hessen et al ), which would comprise 95% of Norwegian lakes. This corresponds well with the observed responses for D. pulex (Prater et al ). By using these species as examples of potential impacts of low—and declining—levels of Ca, it is evident that the effects even over a decadal time‐span may be profound.…”
Section: Discussionsupporting
confidence: 92%
“…As an example of how the declining levels of Ca potentially could affect crustaceans, we use established thresholds for survival of Daphnia magna and D. pulex (0.5–1.0 mg Ca L −1 ) based on both laboratory experiments and field studies (Hessen et al ; Jeziorski et al ; Prater et al ).…”
Section: Methodsmentioning
confidence: 99%
“…While differences in growth rates among treatments can be attributable to [Ca], this effect may also depend on food conditions (e.g., C : P ratios, food quantity) and temperature (Ashforth and Yan ; Prater et al ). For example, the effect of declining Ca on daphniid population growth rate would likely to be much greater at higher food quality (Prater et al ) suggesting that our results may be a conservative indication of future Ca effects in lakes with higher food quantity or quality.…”
Section: Discussionmentioning
confidence: 99%
“…Our ability to predict the effect of Ca decline on the broader zooplankton community, however, remains limited as laboratory and field studies have mainly focused on Ca‐rich Daphnia (Alstad et al ; Hessen and Rukke ; Hessen et al ; Rukke ; Ashforth and Yan ; Jiang et al ; Prater et al ), and body Ca content is not always a reliable predictor for species response to low Ca (Tan and Wang ; Azan et al ). Although field studies have demonstrated increases in the relative abundance of bosminids and Holopedium glacialis as Ca declines (DeSellas et al ; Jeziorski et al ), manipulative experiments to assess causal associations have not been conducted.…”
mentioning
confidence: 99%
“…In addition, Ca could also interact with other elements to affect the behaviour of aquatic invertebrates. For example, many low-calcium lakes are also contaminated with copper, which has been shown to be less toxic at low Ca concentrations [45] and phosphorus, another nutrient that has been in decline in boreal lakes, can also interact with Ca to affect individual growth and survival [53]. Nevertheless, our study is the first, to the best of our knowledge, to show that the synergistic effects of temperature and Ca better explain variation in movement rates by aquatic invertebrates.…”
Section: Discussionmentioning
confidence: 99%